Pollutant Effects and Management of Animal Manure - Fatma Nur Kılıç; Osman Sönmez (Turkish Journal of Agriculture: Food Science and Technology)
Animal manure pollution constitutes a significant environmental issue, particularly in areas with intensive livestock activities. Manure, due to its various pollution loads such as nitrogen, phosphorus, heavy metals, and pathogens, can have adverse effects on soil, water resources, and air quality. Among manure management practices, sustainable methods such as composting, biogas production, and advanced treatment techniques stand out. These methods offer effective solutions for reducing the environmental impact of manure, while also holding the potential to be valued as valuable resources for agriculture and energy production. The growth in the global population along with urbanization has intensified the demand in commerce, industry, and agriculture sectors. This need to satisfy the supply-demand dynamics has led to increased production activities, subsequently giving rise to significant waste management challenges. This review examines the environmental impacts of pollution originating from animal manure, current management strategies, and research developments (R&D) in this field.